Nota aperitiva. Elogio da lentidão. A imparável marcha dos caracóis rumo ao Norte de Portugal: gastronomia estival e fronteiras culturais - Durand, Jean-Yves (Trabalhos de Antropologia e Etnologia, 2020)
The recent evolutions of snail consumption in Portugal, especially in the Minho region, erase an old strong cultural frontier. Anthropology should pay more attention to diffusion phenomena.